2018
DOI: 10.1108/ijchm-07-2017-0409
|View full text |Cite
|
Sign up to set email alerts
|

Impact of individual cultural values on hotel guests’ positive emotions and positive eWOM intention

Abstract: Purpose The purpose of this study is to extend cognitive appraisal theory by integrating customers’ individual difference factors, specifically cultural values. This study examines the effect of individual cultural values on hotel customers’ positive emotions and electronic word-of-mouth (eWOM) creation intention. Design/methodology/approach Online surveys were administered via MTurk. Adults with a recent hotel stay were invited to participate in this study. In all, 331 valid questionnaires were used for dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 65 publications
0
35
0
4
Order By: Relevance
“…Customers' emotions and intensities vary for the same service interaction (Wen et al, 2018). Table 1 combines the appraisal dimensions with the integrated hospitality emotion classifications given in Appendix 1.…”
Section: Theoretical Background 21 Emotional Customer Experience Based On the Appraisal Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Customers' emotions and intensities vary for the same service interaction (Wen et al, 2018). Table 1 combines the appraisal dimensions with the integrated hospitality emotion classifications given in Appendix 1.…”
Section: Theoretical Background 21 Emotional Customer Experience Based On the Appraisal Theorymentioning
confidence: 99%
“…However, existing studies have failed to capture this complexity regarding how emotions are elicited by various sources, leading to the need for more comprehensive studies; (2) Although a more recent study has provided evidence that a service interaction can trigger more than one customer emotion (Maguire and Geiger, 2015), many previous hospitality studies only focused on examining the impact of service-related factors on customers' binary emotions (i.e., pleasant or unpleasant) (Liu and Jang, 2009;Ryu and Jang, 2007). The ways in which service interactions trigger emotional change has not been adequately addressed in prior research; (3) Whilst some studies have found that positive emotions encourage co-creation behaviours such as WOM referrals (Wen et al, 2018), we still know very little about other co-creation behaviours that can be generated by different emotions.…”
Section: Introductionmentioning
confidence: 99%
“…The EWOM variable in this study is a positive assessment of visitors on the activity of sharing information, messages, and pictures to other parties through social media. The measurement of the EWOM variable was adapted from the study of Wen et al, (2017), Indicators for measuring variables are as follows: Leaving positive comments about the tourism destination, Posting positive review about the tourism destination, Uploading photos or videos on the social networks, Giving positive recommendation about the tourism destination, Being active in the social media discussing the tourism destination, and Encouraging others to visit the tourism destination online…”
Section: Epistemic Value Variablementioning
confidence: 99%
“…However, some researchers in recent years were working only for positive emotions because only these matter. Wen, Hu and Kim (2018) [70] examined the effect of individual culture on positive emotions for the recommendation intention. Finally, positive emotions are the principal element to determine the satisfaction of the consumer [71].…”
Section: Introductionmentioning
confidence: 99%